2017
DOI: 10.1002/pd.5096
|View full text |Cite
|
Sign up to set email alerts
|

Fetal intracranial hemorrhage: role of fetal MRI

Abstract: Magnetic resonance imaging is an important tool in prenatal diagnosis of ICH, especially when US describes nonspecific intracranial abnormalities. GMH occurs more frequently and later in pregnancy than non-GMH. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 26 publications
4
32
1
Order By: Relevance
“…The present case was classified as grade 4 due to parenchymal injury. There are several case series diagnosed with USG or MRI in the antenatal period [4]. The first diagnosis of IVH in the intrauterine period was put by Kim et al in 1982 [5].…”
Section: Discussionmentioning
confidence: 99%
“…The present case was classified as grade 4 due to parenchymal injury. There are several case series diagnosed with USG or MRI in the antenatal period [4]. The first diagnosis of IVH in the intrauterine period was put by Kim et al in 1982 [5].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that MRI is an important tool in prenatal diagnosis of ICH, especially when US describes nonspecific intracranial abnormalities. 8 Differential diagnosis of cystic encephalomalacia include encephaloclastic porencephaly and hydrancephaly. The differentiation of an encephaloclastic porencephaly is differentiated from encephalomalacic cavity by its smooth walled, fluid filled cavity in communication with ventricular system while encephalomalacic cavity contains septations and irregular wall composed primarily of reactive astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal GMH-IVH is the most common type of foetal intracranial haemorrhage. [35][36][37] A cranial ultrasound (CUS) on admission allows pre-existing antenatal brain injury to be identified. If antenatal GMH-IVH occurred well before birth, residual findings (ventricular dilatation, intraventricular clots and strands, parenchymal defects) may be subtle (see other relevant paper in this issue).…”
Section: Pathogenesismentioning
confidence: 99%